(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
In the modern era, there is growing worry over youth vigilantism. This is especially true for religious organizations, football, advocacy, and governance. Youth energies should be properly channeled or harnessed for positive, productive goals, as advocated globally. This article aimed to examine the main factors contributing to the detrimental effects of juvenile vigilantism and the role that the government has played in these historical events. Mixed techniques were employed in the study, guided by the political vigilantism theory. With the help of stratified and purposive sampling procedures, four important informants in the Bolgatanga Municipality were interviewed for the report, completing a triangulation process. The research discovered that, in one way or another, instability, unemployment or idleness, police corruption, illiteracy, bad police-community relations, and ineffective policing had